Hedge Fund Flows and Performance Streaks: How Investors Weigh Information - Baquero, Guillermo; Verbeek, Marno (Management Science, 2022)
Cash flows to hedge funds are highly sensitive to performance streaks, a streak being defined as subsequent quarters during which a fund performs above or below a benchmark, even after controlling for a wide range of common performance measures. At the same time, streaks have limited predictive power regarding future fund performance. This suggests investors weigh information suboptimally, and their decisions are driven too strongly by a belief in continuation of good performance, consistent with the “hot hand fallacy.” The hedge funds that investors choose to invest in do not perform significantly better than those they divest from. These findings are consistent with overreaction to certain types of information and do not support the notion that sophisticated investors have superior information or superior information processing abilities.